THE EFFECT OF LIQUIDITY AND WORKING CAPITAL ON CORPORATE VALUES WITH PROFITABILITY AS MODERATING VARIABLES IN MANUFACTURING COMPANIES LISTED ON IDX - Pratiwi, Hanna; Ronni Andri Wijaya; Desi Permata Sari; Riska Maiputri Yengsih (Dinasti International Journal of Economics, Finance & Accounting, 2020)
This study aims to examine and analyze the effect of Liquidity (X1) and Working Capital (X2) on Company Value (Y) with Profitability (Z) as a moderating variable. The study was conducted on manufacturing companies listed on the Indonesia Stock Exchange with a research period of 2014-2018. The sample selection method used is porpusive sampling and obtained as many as 22 manufacturing companies as samples with 110 observations. Based on the partial test results there is a significant effect between liquidity on firm value, there is no influence between working capital on firm value. Liquidity and working capital together have a significant effect on firm value. Profitability is not able to moderate liquidity to the value of the company. Profitability is able to moderate working capital to the value of the company. Simultaneously liquidity and working capital have a significant effect on firm value. The contribution of the independent variable that is liquidity and working capital in influencing the dependent variable that is the value of the company is 87.23%.